Rice land races of Kerala State of India: A documentation - Latha M; Abdul Nizar M; Abraham Z; Joseph John K.; R. Asokan Nair; Mani S. and M. Dutta (International Journal of Biodiversity and Conservation, 2013)
Rice landraces of Kerala State of India are named based on cropping season, growing conditions, crop duration, morphological features, color of seed and other specific traits, if any. The collections of landraces of Kerala are classified as rare, very rare and common. A part of these collected accessions have been characterized. DIVA-GIS was used to map the collection site, which showed that the collections made are well distributed throughout Kerala but very meager collections are represented from Thiruvananthapuram and Pathanamthitta Districts. Till about 20 years back, all the paddy fields in Kerala were being cultivated with various landraces of rice during the southwest and northeast monsoon seasons. Currently, these paddy fields are being progressively filled with soil transported from other places and converted into building sites or sites for growing other upland crops. As a result of this, a large number of primitive cultivars and local landraces of rice have been lost. Genetic erosion can be assessed and target areas for collection in diversity rich area can be predicted based on resurvey of the collection localities and mapping the collection localities using DIVA-GIS tool. The present paper describes the rice landraces of Kerala with their specific location from where they have been collected.